Health care needs and services available for elders in the Batticaloa district - Arulanandem, K.; Jayawickramaraja, P. T.; Hettige, S.; Ramanayake, R. P. J. C.; Kisokanth, G. (My University, 2018)
The global and national ageing population led to much health, social and economic concerns. Thus, present study aimed at addressing the health care needs of elders and assessing the availability of health, social services in Batticaloa district. This community based cross sectional descriptive study was conducted in Batticaloa district with 845 elders who were selected by proportionate random sampling and interviewer administrated questionnaire was used as a major component. Most of the elders (78%) were in the young old category and majority of them (56.6%) were females and most of elders (77%) were in poor socio economic status. The identified long standing medical problems amongst elders were hypertension (39%), muscular skeletal problems (32%) and bronchial asthma (18%) were also identified. Most of the elders (88%) sought medical treatment in outpatient department as first contact at government hospitals while around half of them had followed clinics for chronic conditions. This study also showed that the health system in Batticaloa district lacked geriatric services and elders were not treated as a special group. In the context of social services, most of the elders were unaware and thus were not benefitted by the currently existing social security. Health seeking behavior and accessibility of health and social services were not adequately met for elders. Thus, there is a need to improve their wellbeing by strengthening primary care in national health system.
Keywords: elders; Batticaloa; health seeking; services